Sosialisasi Penggunaan Game Matematika Bagi Siswa Madrasah Ibtidaiyah Al Hidayah Makassar - Indrabayu -; Ingrid Nurtanio; Christoforus Yohannes; Zulkifli Tahir; Ais Prayogi; Anugrayani Bustamin; Riny Yustica Dewi; Rizka Irianty (JURNAL TEPAT : Teknologi Terapan untuk Pengabdian Masyarakat, 2020)
Mathematics is an important subject taught in schools. Learning mathematics gives students' the ability to reason and develop their mindset. However, many students feel less interested in mathematics. This results in students’ poor learning achievesment. One solution to increase student interest in learning is to use tools that utilize technology. The community service carried out at Madrasah Ibtidaiyah Al Hidayah Makassar aims to provide new insights for students regarding digital learning methods and materials at school. It also aims to foster motivation to learn mathematics, which is often seen as a fearful subject by students. The implementation of this community service is divided into 2 stages, which are the stage of socializing the technology-based learning methods, in this case using android smartphones, and the training stage on how to use the Mathology educational applications. This community service is also a venue for disseminating the research regarding the application ofinteractive learning media from Department of Informatics Engineering, Engineering Faculty, UNHAS.